Comparative analysis of rhizosphere microbial communities and secondary metabolites in cultivated Rheum officinale from different regions of China - Wang, Yan; Yan, Feng; Liang, Yujie; Hu, Xiaochen; Gao, Jing; Zhang, Mingying; Yan, Yonggang; Zhang, Gang; Li, Yimin (Frontiers in Plant Science, 2025)
Rheum officinale Baill., a medicinal herb rich in anthraquinones and tannins, exhibits region-specific variation in bioactive compound accumulation. Given the well-documented pharmacological properties of R. officinale Baill. including its laxative, antibacterial, anti-inflammatory and regulating intestinal function, this study integrated Illumina sequencing of rhizosphere microbiomes, HPLC quantification of 10 active components (e.g., rhein, physcion), and soil analysis across three cultivation regions Shaanxi (ZB), Hubei (HB), Chongqing (CQ). Results demonstrated significant regional disparities: ZB showed highest rhein and catechin levels, while CQ accumulated more physcion. Microbial diversity followed the order ZB>HB>CQ, with Proteobacteria and Ascomycota dominating bacterial and fungal communities, respectively. Soil pH, moisture (SWC), and Zn/Cu content strongly correlated with microbial structure. Notably, Rokubacteriales was significantly positively associated with anthraquinones accumulation. These findings suggest that soil properties modulate microbial communities, which in turn regulate secondary metabolite biosynthesis through nutrient cycling (e.g., nitrogen/phosphorus metabolism). This study elucidates the tripartite interaction of soil-microbe-metabolite networks in R. officinale Baill., providing insights for geoherbalism optimization. Future research will focus on optimizing R. officinale Baill. cultivation through soil condition management to enhance both quality and yield.